Regeneration of tert-butylhydroquinone by tea polyphenols. (May 2017) - Guo, Yafang; Guo, Yahui; Xie, Yunfei; Cheng, Yuliang; Qian, He; Yao, Weirong
Abstract: To study the antioxidant capacity (AC) regeneration of tert -butylhydroquinone (TBHQ) by tea polyphenols (TPs), a separable system has been designed for its evaluation. The AC values of three natural food matrices (liquorice, oat, and ginger) and TBHQ regenerated by TPs were all higher than their controls, and similar to the initial values ( p < 0.05). The average regeneration efficiency (RE) value was 1.49 for these three natural food matrices, and 0.82 for TBHQ. Electron paramagnetic resonance spectroscopy analysis has revealed the synergistic effect of TBHQ and TPs, which arose from the regeneration of TBHQ by TPs. The RE value of TBHQ regeneration by TPs embedded in a gelatine membrane was 0.51. The results demonstrated that TPs showed a capacity for regenerating TBHQ, indicating a potential application in regenerative packaging, whereby one antioxidant would be added to the food matrix, with another one as the regenerator incorporated into the packaging material. Graphical abstract: Highlights: A systematic investigation has revealed that tea polyphenols can regenerate TBHQ. A separable system has been designed for the evaluation of the regeneration. The innovative concept of regenerating package is that one antioxidant can be added to the food matrix, with another one as the regenerator incorporated into the packaging materials.